(i)
Given data:
The given expression is -1/8 (X-24)+1/2(X+4)=X+15.
The given expression can be written as,
![\begin{gathered} -(1)/(8)(X-24)+(1)/(2)(X+4)=X+15 \\ (-(X-24)+4(X+4))/(8)=X+15 \\ -X+24+4X+16=8(X+15) \\ 3X+40=8X+120 \\ -5X=80 \\ X=-16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j6q4y5a5qbb6sm8x61ww7w0pr45rowjva1.png)
Thus, the value of X is -16.
(ii)
Given data:
The given expression is 12(X+2)-4x=4(2X+11)-20.
The given expression can be written as,
![\begin{gathered} 12(X+2)-4X=4(2X+11)-20 \\ 12X+24-4X=8X+44-20 \\ 8X+24=8X+24 \\ 8X-8X=24-24 \\ 0=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qupt9w98p0w6vv2u7lkqdz01xs7ccnzz0a.png)
Thus, the above equation is true for all values of x.